Memetakan Lanskap Akademik tentang Fake News di Indonesia: Kajian Bibliometrik - Iqbal Ramadhani Mukhlis; Mohammad Syarrafah; Iswanda F. Satibi; Nambi Sembilu (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This bibliometric study aims to chart trends, thematic foci, and collaboration networks of fake-news research in Indonesia, to uncover methodological and regulatory gaps hindering hoax mitigation, and to formulate evidence-based policy agendas. Data were harvested from Lens.org on 9 May 2025 using the query “fake news” AND “Indonesia”. The initial 846 records were screened for document type and duplicates, yielding 753 publications. Performance indicators (h-index, citations, open-access status) and science-mapping techniques (co-word, co-authorship, temporal overlays) were applied via Lens.org analytic tools. Findings reveal three publication waves—a formative period (2008-2014), an electoral surge (2015-2019), and a pandemic spike (2020-2024). The corpus reports an h-index of 42, roughly 7 500 citations, and 71 % open-access availability. Political misinformation and health-related disinformation dominate the discourse, while methodological evolution from bag-of-words classifiers to transformer architectures is still constrained by small, single-modal datasets, limiting cross-domain accuracy. Collaboration networks are led by Universitas Indonesia, Universitas Gadjah Mada, and BINUS University, with international co-authorship accounting for only 14 % of outputs. Persistently low digital literacy and overly broad anti-hoax regulations generate a journalistic chilling effect. Strategic recommendations include creating a CC-BY multimodal national corpus of at least 100 000 annotated items, deploying real-time AI moderation through the KominfoAId initiative, implementing sustained train-the-trainer literacy programmes for teachers, enacting a rights-based Digital Rights Bill, and conducting annual longitudinal surveys across 34 provinces to track the societal impact of hoaxes.